Parameters of life quality in the treatment efficiency estimation of patients with glial brain tumors - V. D. Rozumenko; A. P. Khoroshun (Ukrainian Neurosurgical Journal, 2007)
In the process of patients with gliomas complex treatment their quality of life was researched. It was found that before treatment the life quality was estimated as low and medium, it depended on localization, gystobiology, preoperative neurological deficit severity, age and gender. After postoperative treatment patients quantity with Karnofsky scale index 70 scores and more grew up to 37,2%, with medium and high levels of life quality by the social-psychology adaptation scale increased to 39%.